Disease Activity and Anti-Cyclic Citrullinated Peptide (Anti-CCP) Antibody in Saudi RF-Negative Rheumatoid Arthritis Patients - Mohammad-Ayman A. Safi; Dhia A. Houssien; David L. Scott (Journal of King Abdulaziz University: Medical Sciences, 2023)
An investigation of disease activity and prevalence of anti-cyclic citrullinated peptide in 200 Saudi Rheumatoid Factor-negative rheumatoid arthritis patients; 164 females and 36 males; with a mean age of 45.14 years (SD = 12.54). 97% were receiving disease modifying therapy; as single (77%) and as combination treatment (20%). Hydroxychloroquine was the most used drug (92 patients). Prevalence of anti-cyclic citrullinated peptide was 61/200 (30.5%). Disease activity scores for 28 joints were low (< 3.2) in 2 (1%) patients, moderate (3.2-5.1) in 38 (19%), and high (> 5.1) in 160 (80%). No significant differences (p > 0.05) between positive and negative anti-cyclic citrullinated peptide patients for Disease Activity Score for 28 Joints, morning stiffness, C-reactive protein, disease duration, and presence of mixed diseases. A substantial number (30.5%) of rheumatoid factor negative patients are anti-cyclic citrullinated peptide positive therefore anticyclic citrullinated peptide antibodies are a useful diagnostic tool for rheumatoid arthritis in RF-ve rheumatoid arthritis patients from Saudi Arabia. In conclusion, there is no difference in the severity or the treatment of rheumatoid arthritis patients with RFve/CCP+ve compared to RFve/ CCP-ve patients. Therefore, anti-cyclic citrullinatedpeptide test is not useful in predicting disease activity and deciding on management in these patients.